2020
DOI: 10.1001/jamanetworkopen.2019.19396
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a Machine Learning Model Applied to Harmonized Electronic Health Record Data for the Prediction of Incident Atrial Fibrillation

Abstract: IMPORTANCE Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia, and its early detection could lead to significant improvements in outcomes through the appropriate prescription of anticoagulation medication. Although a variety of methods exist for screening for AF, a targeted approach, which requires an efficient method for identifying patients at risk, would be preferred. OBJECTIVE To examine machine learning approaches applied to electronic health record data that have been harmonized to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
76
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 80 publications
3
76
1
Order By: Relevance
“…The process of the evolution of the distance regularization level set curve is the process of continuously reducing ε in equation 6and eventually approaching zero [52]. This process is expressed by differential equations, and the expression is shown in 7:…”
Section: A Aggregation Model Based On Guayes Hypothesismentioning
confidence: 99%
“…The process of the evolution of the distance regularization level set curve is the process of continuously reducing ε in equation 6and eventually approaching zero [52]. This process is expressed by differential equations, and the expression is shown in 7:…”
Section: A Aggregation Model Based On Guayes Hypothesismentioning
confidence: 99%
“…8 , 9 It is clear that the performance of any AI model broadly depends on its reliability and its ability to generalize to the setting and population in which it is applied, rather than its performance represented by the training and test data alone. 10 However, the characteristics of the data necessary to assess how these predictive models perform are not being adequately reported in the literature, 11 leaving uncertainty and doubt about the application in the broader healthcare setting. An empirical evaluation of 81 studies comparing AI models against clinicians showed major problems with lack of transparency, bias, and unjustified claims, likely because key details about the studies were often missing.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, our recent study showed an alarming lack of transparency of ML models developed in research studies. 11 Therefore, we need transparency in the reporting of the design, development, evaluation, and validation of AI models in health care to achieve and retain confidence and trust for all the stakeholders.…”
Section: Introductionmentioning
confidence: 99%
“…However, these existing models required variables not typically available as structured electronic health record (EHR) fields (e.g., electrocardiogram [ECG] parameters). Newer attempts at EHR-based models have required extra steps of data harmonization [ 9 ] or use of long prediction horizons and require non-missing data or oft-unstructured data [ 10 ]. Other efforts use available data from the EHR, but make a prediction for 10-year risk using binned risk categories [ 11 ], or rely on claims databases and make predictions on simple cross-sectional association [ 12 ].…”
Section: Introductionmentioning
confidence: 99%